Soil water content at the catchment level and plant water status relationships in a Mediterranean Quercus ilex forest - Bellot, J.; Ortiz de Urbina, J. M. (Journal of Hydrology, 2008)
This paper presents an analysis of the forest hydrology and plant water status interaction, focusing on the relationship between the hydrological water balance at the catchment level and the predawn leaf water potential of the species Quercus ilex (holm oak). The catchment water balance approach was applied to a Mediterranean watershed forested with holm oak to evaluate the daily soil water reserve at the catchment level. After this, evapotranspiration and soil water content were combined to estimate the potential soil water reserve and evaluate plant water status at the catchment level. A close relationship was detected between leaf water potential and the soil water reserve, and was ﬁtted to a negative exponential curve to estimate predawn leaf water potential from a hydrological database. The proposed equation can help to predict the frequency, intensity, and length of droughts potentially capable of causing structural damage to the forest, from the hydrological time series records.
Keywords: Catchments; Plant water status; Predawn water potential; Quercus ilex; soil water; water balance